International experts or Fascist envoys?: Alberto Theodoli and Pietro Stoppani at the League of Nations - Tollardo, Elisabetta (New global studies, 2016)
This article seeks to shed new light on the complex nature of Italian agency in the League of Nations (LoN) and the Italians’ involvement in the international community that characterised Geneva in the interwar period. By analysing the actions and the networks of the Italians who worked in the League’s machinery, this article reveals the extent to which they were part of an international society emerging in Geneva. Through the experiences of Alberto Theodoli, chairman of the Permanent Mandates Commission, and Pietro Stoppani, director of the Economic Relations Section, this study concludes that Italian experts were fully part of the international society that flourished in interwar Geneva, being members of international networks and using their position to promote their agendas. However, these Italians were influenced in different ways by the Fascist regime and their attachment to the League’s internationalism varied. The article shows how the Fascist government realised the potential of the LoN world for promoting its foreign policy goals and legitimising the regime. Fascist Italy valued Geneva as a central forum for international relations and as a place where it could further its imperial ambitions.